Perovskite crystalline silicon laminated solar cell and preparation method thereof

By using the water film layer and annealing-UVO treatment on the surface of the NIOX transmission layer, improve the infiltration of the SAM layer, solve the problem of uneven coating on the surface of the perovskite layer, significantly improved the perovskin/crystal silicon overlap layer solar cell battery Optical conversion efficiency and reliability.

CN119365038APending Publication Date: 2025-01-24ZHEJIANG AIKO SOLAR ENERGY TECH CO LTD +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411462558.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the existing perovskite/crystalline silicon stacked solar cells, the SAM layer has poor wetting properties, resulting in uneven surface coating of the perovskite layer, limiting the improvement of battery performance.

Method used

Use the water film layer on the surface of the NIOX transmission layer, and through annealing and UVO treatment to improve the infiltration of the SAM layer, thereby achieving a uniform full coverage of the perovskite layer on the SAM layer surface.

Benefits of technology

By improving the infiltration of the SAM layer, the uniformity and stability of the perovskite layer is significantly improved, and the overall photoelectric conversion efficiency and reliability of the oscillant ore/crystal silicon layer solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365038A_ABST
    Figure CN119365038A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite crystalline silicon laminated solar cell and a preparation method thereof. The preparation method comprises the following steps: sequentially preparing an ITO tunneling layer and a NiOx transmission layer on the surface of a crystalline silicon bottom cell; the surface of the NiOx transmission layer is coated with water, annealing and UVO treatment are conducted in sequence, and a water film layer is obtained; and sequentially preparing an SAM layer, a perovskite layer, an interface passivation layer, an electron transport layer, a SnO2 layer, an IZO layer and a metal electrode layer on the surface of the water film layer to obtain the perovskite crystalline silicon laminated solar cell. According to the method, the water film layer is used on the NiOx surface, annealing and UVO treatment are combined, more hydroxyl groups are obtained on the surface, SAM components are modified, the wettability of SAM is further changed, uniform full coverage of the perovskite film layer on the SAM surface can be achieved, the uniformity and stability of the perovskite layer are remarkably improved, and the service life of the SAM is prolonged. Therefore, the overall photoelectric conversion efficiency and reliability of the perovskite / crystalline silicon laminated solar cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a perovskite crystalline silicon stacked solar cell and a preparation method thereof. Background Art

[0002] The rapid development of the photovoltaic industry has promoted the continuous progress of solar cells. Current solar cells include monocrystalline silicon solar cells, polycrystalline silicon solar cells, amorphous silicon solar cells and compound semiconductor solar cells. Among them, monocrystalline silicon solar cells and polycrystalline silicon solar cells have mature technology and low cost. Although amorphous silicon solar cells have low cost, they have low conversion efficiency and are prone to cavity effect when working outdoors for a long time, resulting in the attenuation of battery performance. Compound semiconductor solar cells are expensive due to the special nature of the materials and require special working conditions, which limits their large-scale promotion and use.

[0003] On the basis of traditional crystalline silicon solar cells, stacking perovskite solar cells with crystalline silicon solar cells can reduce the light absorption loss of crystalline silicon cells, and at the same time, utilize the high spectral response of perovskite solar cells to achieve the purpose of improving the overall solar cell conversion efficiency. However, the processes of perovskite solar cells and crystalline silicon solar cells are different. During the stacking preparation process, the perovskite layer is prone to chemical reaction with the surface of the crystalline silicon cell, which reduces the performance of the perovskite layer, thereby limiting the performance of the stacked cell.

[0004] At present, perovskite / crystalline silicon tandem solar cells have become the mainstream material used in the photovoltaic field, and the highest efficiency can reach 33.9%. In order to further improve the power conversion efficiency of tandem solar cells, the relevant film layers of perovskite cells can be optimized. Among them, the self-assembled molecular layer (SAM) has become the main hole transport layer of the current perovskite cell, but in the tandem cell structure, due to the wettability problem of the high-performance Me-4PACz SAM layer, it will be impossible to obtain a uniform perovskite film layer on its surface, which is not conducive to the preparation of perovskite and crystalline silicon tandem solar cells. Summary of the invention

[0005] The main purpose of the present invention is to provide a perovskite crystalline silicon tandem solar cell and a preparation method thereof, so as to solve the problems of poor wettability of the SAM layer and uneven surface coating of the perovskite layer in the prior art perovskite crystalline silicon tandem solar cell.

[0006] In order to achieve the above object, according to one aspect of the present invention, a method for preparing a perovskite crystalline silicon stacked solar cell is provided. The perovskite crystalline silicon stacked solar cell comprises a crystalline silicon bottom cell, an ITO tunneling layer, a NiO xtransmission layer, water film layer, SAM layer, perovskite layer, interface passivation layer, electron transmission layer, SnO2 layer, IZO layer, metal electrode layer, x is 1-2; the preparation method comprises the following steps: step S1, sequentially preparing an ITO tunneling layer, a NiO x Transport layer; Step S2, in NiO x Water is coated on the surface of the transport layer to obtain a water film layer preparatory layer, and the water film layer preparatory layer is sequentially annealed and UVO treated to obtain a water film layer; step S3, a SAM layer is prepared on the surface of the water film layer; step S4, a perovskite layer is prepared on the surface of the SAM layer; step S5, an interface passivation layer, an electron transport layer, a SnO2 layer, an IZO layer, and a metal electrode layer are sequentially prepared on the surface of the perovskite layer to obtain a perovskite crystalline silicon stacked solar cell.

[0007] Furthermore, in step S2, the annealing temperature is 80-120° C. and the time is 5-15 min.

[0008] Furthermore, in step S2, the UVO treatment time is 10 to 15 minutes.

[0009] Further, in step S2, in NiO x The surface of the transmission layer is spin-coated or sprayed with water to obtain a water film layer preparation layer.

[0010] Furthermore, the spin coating speed is 2000-4000 rpm, the time is 20-40 s; and / or the spraying pressure is 100-200 Kpa, the spraying speed is 2-10 mm / s, the nozzle size is 0.2-0.5 mm, and the NiO x The distance of the transmission layer is 100 to 500 μm.

[0011] Furthermore, in step S2, the thickness of the water film preparation layer is 10-20 μm.

[0012] Furthermore, in step S3, the raw material of the SAM layer includes a main component and a solvent, and the main component includes one or more of Me-4PACz, MeO-4PACz and MeO-2PACz; preferably, in the raw material of the SAM layer, the mass concentration of the main component is 0.5 to 3 mg / mL.

[0013] Furthermore, in step S3, the raw material of the SAM layer is spin-coated or spray-coated on the surface of the water film layer, and then post-annealing is performed to obtain the SAM layer.

[0014] Furthermore, the spin coating speed is 2000-4000 rpm, and the time is 20-40 s; and / or the spraying pressure is 100-200 Kpa, and the spraying speed is 2-10 mm / s; and / or the post-annealing temperature is 100-120° C., and the time is 5-10 min.

[0015] According to another aspect of the present invention, a perovskite crystalline silicon stacked solar cell is provided, which is obtained using the above-mentioned preparation method of the present invention.

[0016] Applying the technical solution of the present invention, by x A water film layer is used on the surface, combined with annealing and UVO treatment, to obtain more hydroxyl groups on its surface, more anchored SAM components, modify the SAM components, and finally prepare a uniform perovskite film layer on its surface. By changing the underlying structure of the SAM and then changing the wettability of the SAM, a uniform full coverage of the perovskite film layer on the SAM surface can be achieved, significantly improving the uniformity and stability of the perovskite layer, thereby improving the overall photoelectric conversion efficiency and reliability of the perovskite / crystalline silicon laminated solar cell. The method of the present invention has low cost, simple operation, can be prepared on a large scale, is green and pollution-free, and is suitable for commercial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 A schematic diagram of the structure of a perovskite crystalline silicon stacked solar cell according to an embodiment of the present invention is shown.

[0019] The above drawings include the following reference numerals:

[0020] S1, crystalline silicon bottom cell; S2, ITO tunneling layer; S3, NiO x Transport layer; S4, water film layer; S5, SAM layer; S6, perovskite layer; S7, interface passivation layer; S8, electron transport layer; S9, SnO2 layer; S10, IZO layer; S11, metal electrode layer. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0022] As described in the background of the present invention, the prior art has the problem that the SAM layer in the perovskite crystalline silicon tandem solar cell has poor wettability and the surface coating of the perovskite layer is uneven. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a perovskite crystalline silicon tandem solar cell is provided. The perovskite crystalline silicon tandem solar cell comprises a crystalline silicon bottom cell, an ITO tunneling layer, and a NiO xtransmission layer, water film layer, SAM layer, perovskite layer, interface passivation layer, electron transmission layer, SnO2 layer, IZO layer, metal electrode layer, x is 1-2; the preparation method comprises the following steps: step S1, sequentially preparing an ITO tunneling layer, a NiO x Transport layer; Step S2, in NiO x Water is coated on the surface of the transport layer to obtain a water film layer preparatory layer, and the water film layer preparatory layer is sequentially annealed and UVO treated to obtain a water film layer; step S3, a SAM layer is prepared on the surface of the water film layer; step S4, a perovskite layer is prepared on the surface of the SAM layer; step S5, an interface passivation layer, an electron transport layer, a SnO2 layer, an IZO layer, and a metal electrode layer are sequentially prepared on the surface of the perovskite layer to obtain a perovskite crystalline silicon stacked solar cell.

[0023] Generally, the poor direct contact performance between the SAM layer and the perovskite is related to the SAM bottom structure. The present invention changes the SAM bottom structure and then changes the wettability of the SAM layer, so that the perovskite film can be evenly covered on the surface of the SAM layer. The present invention first prepares the ITO tunneling layer, NiO x transport layer; then on NiO x Water is coated on the surface of the transmission layer to obtain a water film preparatory layer, and the water film preparatory layer is annealed. After the annealing treatment, the surface of the water film layer will be more stable, and then UVO treatment is performed. After UVO treatment, the number of hydroxyl groups on the surface of the film layer can be increased, so that more SAM molecules are anchored on the surface of the film layer, thereby improving the performance of the battery. Ultraviolet ozone treatment can also increase the surface energy, creating favorable conditions for the preparation of the SAM layer. After the water film layer is obtained, the SAM layer is prepared on its surface.

[0024] The present invention adopts NiO x The surface is treated with a water film layer, combined with annealing and UVO treatment, to obtain more hydroxyl groups on its surface, more anchoring SAM layer components, and to modify the SAM layer to improve its wettability. The perovskite layer can be evenly coated on the surface of the SAM layer to prepare a fully covered perovskite layer, which significantly improves the uniformity and stability of the perovskite layer, thereby improving the overall photoelectric conversion efficiency and reliability of the perovskite / crystalline silicon stacked solar cell. Finally, an interface passivation layer, an electron transport layer, a SnO2 layer, an IZO layer, and a metal electrode layer are sequentially prepared on the surface of the perovskite layer to obtain a perovskite crystalline silicon stacked solar cell.

[0025] Based on the adjustable bandgap of perovskite, it can match the bandgap of crystalline silicon with better performance to achieve maximum utilization of light source. At the same time, crystalline silicon battery itself is relatively stable and efficient, so it is the best choice to form a laminated structure battery with perovskite. The manufacturing method of the present application significantly improves the uniformity and stability of the perovskite layer by introducing a water film layer and a SAM layer, thereby improving the overall efficiency and reliability of perovskite / crystalline silicon laminated solar cells. The application of this technology not only promotes the development of perovskite solar cells, but also provides a new way to improve the performance of crystalline silicon solar cells, with significant economic and environmental benefits. In practical applications, this technology can be widely used in various solar power generation systems to promote the popularization and application of green energy.

[0026] In a preferred embodiment, in step S2, the annealing temperature is 80-120° C. and the time is 5-15 min. The above conditions can increase the anchoring strength of SAM while fully removing the residual solvent, and will not affect the subsequent coating of perovskite, which is conducive to achieving uniform coating of the perovskite raw material solution and obtaining a perovskite film layer with better crystal quality.

[0027] To further improve the surface activity and facilitate high-purity surface treatment, in a preferred embodiment, in step S2, the UVO treatment time is 10 to 15 minutes. Under the above conditions, UVO treatment can more fully activate the hydroxyl groups on the surface of the film layer, thereby further improving the wettability of the SAM surface by affecting the anchoring mode of the SAM, thereby improving the film quality of the perovskite.

[0028] In order to make the prepared water film layer more uniform, to more effectively improve the interface properties, to reduce charge recombination, and to provide a more suitable substrate for subsequent SAM layer preparation, in a preferred embodiment, in step S2, NiO x The surface of the transmission layer is spin-coated or sprayed with water to obtain a water film layer preparation layer.

[0029] For similar reasons, in a preferred embodiment, the spin coating speed is 2000-4000 rpm, the time is 20-40 s; and / or the spraying pressure is 100-200 KPa, the nozzle size is 0.2-0.5 mm, and the spraying speed is 2-10 mm / s, which is similar to NiO x The distance of the transmission layer is 100 to 500 μm. This combination of parameters can obtain a more uniformly covered SAM layer, and is simple and easy to operate, which is conducive to large-scale production.

[0030] In a preferred embodiment, in step S2, the thickness of the water film preparation layer is 10-20 μm. A thin and uniform water film layer can more effectively improve the NiO xThe anchoring strength between the layer and the subsequent SAM layer improves the charge transfer efficiency and is suitable for large-scale production, especially in the scenario where the battery stability and conversion efficiency need to be improved. When the water film layer preparation layer is prepared by spin coating, the thickness can be controlled by the solution concentration. When the water film layer preparation layer is prepared by spraying, the thickness can be controlled by the number of spraying times. These are understandable to those skilled in the art and can be adjusted routinely according to actual production conditions, and will not be repeated here.

[0031] In order to further reduce interface defects and improve battery reliability and stability, in a preferred embodiment, in step S3, the raw materials of the SAM layer include a main component and a solvent, and the main component includes one or more of Me-4PACz, MeO-4PACz and MeO-2PACz; preferably, in the raw materials of the SAM layer, the mass concentration of the main component is 0.5-3 mg / mL. By adjusting these parameters, better interface effects can be achieved, the interface hole transfer efficiency can be increased, and charge recombination can be reduced to further improve the photoelectric conversion efficiency.

[0032] In order to further optimize the deposition conditions of the perovskite layer, improve the quality of the SAM film layer, improve the accuracy and efficiency, and improve the conversion efficiency of the battery, in a preferred embodiment, in step S3, the raw material of the SAM layer is spin-coated or sprayed on the surface of the water film layer, and then post-annealing is performed to obtain the SAM layer.

[0033] In a preferred embodiment, the spin coating speed is 2000-4000 rpm, the time is 20-40s; and / or the spraying pressure is 100-200 Kpa, the spraying speed is 2-10 mm / s; and / or the post-annealing temperature is 100-120°C, the time is 5-10 min. By adjusting these parameters, the coating effect of the later perovskite layer can be further optimized, its uniformity and stability can be improved, thereby improving the performance of the overall battery.

[0034] Among them, crystalline silicon bottom cell, ITO tunneling layer, NiO x The transport layer, perovskite layer, interface passivation layer, electron transport layer, SnO2 layer, IZO layer, and metal electrode layer can be prepared using conventional materials and conventional preparation methods in the art. For example, the ITO tunneling layer is prepared by magnetron sputtering; the NiO xTransport layer; prepare the perovskite layer by spin coating, scraping, spraying or soaking, the material of the perovskite layer can be conventional materials in the field, without special limitation; prepare the interface passivation layer by spin coating, spraying or scraping, the material of the interface passivation layer can be one or more of alkali metal fluoride (such as LiF), piperazine compound (such as PI, PDI), organic amine salt (such as TEABr); prepare the electron transport layer by spin coating, spraying, scraping or evaporation, the electron transport layer is PCBM layer or C60 layer; prepare SnO2 layer by ALD (atomic layer deposition); prepare IZO layer by magnetron sputtering; prepare metal electrode layer by evaporation or screen printing. These are understandable to those skilled in the art and will not be repeated here.

[0035] In another typical embodiment of the present invention, a perovskite crystalline silicon stacked solar cell is provided, which is obtained using the above-mentioned preparation method of the present invention. Based on the modification of the wettability of the SAM layer by the water film layer, the perovskite layer can be evenly coated, and the perovskite layer has a significantly improved photoelectric conversion efficiency.

[0036] Typically but not limiting, in step S2, the annealing temperature is 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or a range consisting of any two of them, and the annealing time is 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min or a range consisting of any two of them.

[0037] Typically but not limiting, in step S2, the UVO treatment time is 10 min, 11 min, 12 min, 13 min, 14 min, 15 min or a range consisting of any two of them.

[0038] Typically but not limiting, in step S3, the post-annealing temperature is 100°C, 105°C, 110°C, 115°C, 120°C or a range consisting of any two of them, and the time is 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or a range consisting of any two of them.

[0039] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0040] Unless otherwise specified, the materials used in the following examples and comparative examples can be conveniently purchased from the market or prepared using conventional methods in the art.

[0041] Example 1

[0042] A perovskite crystalline silicon tandem solar cell, such as Figure 1 As shown, it includes a crystalline silicon bottom cell S1, an ITO tunneling layer S2, and a NiO x Transport layer S3 (x is 2), water film layer S4, SAM layer S5 (Me-4PACz), perovskite layer S6 (Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.73 Br 0.27 )3), interface passivation layer S7 (PI), electron transport layer S8 (PCBM), SnO2 layer S9, IZO layer S10, metal electrode layer S11 (Ag); the preparation method comprises the following steps:

[0043] (1) Obtaining a crystalline silicon bottom cell;

[0044] (2) Preparing an ITO tunneling layer on the surface of the crystalline silicon bottom cell by magnetron sputtering;

[0045] (3) Preparation of NiO on the surface of ITO tunneling layer by magnetron sputtering x Transport layer;

[0046] (4) In NiO x The surface of the transport layer was spin-coated with water (rotation speed of 3000 rpm, time of 30 s) to obtain a water film layer preparatory layer, and the water film layer preparatory layer was sequentially annealed (temperature of 100°C, time of 10 min) and UVO treated (time of 12 min) to obtain a water film layer (thickness of 15 μm);

[0047] (5) spin coating (rotation speed of 3000 rpm, time of 30 s) a Me-4PACz isopropanol solution (mass concentration of 2 mg / mL) on the surface of the water film layer, and then post-annealing (temperature of 110 °C, time of 8 min) to prepare a SAM layer;

[0048] (6) Preparing a perovskite layer on the surface of the SAM layer by spin coating;

[0049] (7) preparing an interface passivation layer on the surface of the perovskite layer by spin coating;

[0050] (8) preparing an electron transport layer on the surface of the interface passivation layer by spin coating;

[0051] (9) Preparing a SnO2 layer on the surface of the electron transport layer by ALD;

[0052] (10), preparing an IZO layer on the surface of the SnO2 layer by magnetron sputtering;

[0053] (11) A metal electrode is prepared on the surface of the IZO layer by evaporation to obtain a perovskite crystalline silicon stacked solar cell.

[0054] Example 2

[0055] A perovskite crystalline silicon stacked solar cell, comprising a crystalline silicon bottom cell S1, an ITO tunneling layer S2, and a NiO x Transport layer S3 (x is 2), water film layer S4, SAM layer S5 (Me-4PACz), perovskite layer S6 (Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.73 Br 0.27 )3), interface passivation layer S7 (PI), electron transport layer S8 (PCBM), SnO2 layer S9, IZO layer S10, metal electrode layer S11 (Ag); the preparation method comprises the following steps:

[0056] (1) Obtaining a crystalline silicon bottom cell;

[0057] (2) Preparing an ITO tunneling layer on the surface of the crystalline silicon bottom cell by magnetron sputtering;

[0058] (3) Preparation of NiO on the surface of ITO tunneling layer by magnetron sputtering x Transport layer;

[0059] (4) In NiO x The surface of the transport layer was spin-coated with water (rotation speed of 3000 rpm, time of 30 s) to obtain a water film layer preparatory layer, and the water film layer preparatory layer was sequentially annealed (temperature of 80°C, time of 15 min) and UVO treated (time of 10 min) to obtain a water film layer (thickness of 15 μm);

[0060] (5) spin coating (rotation speed of 3000 rpm, time of 30 s) a Me-4PACz isopropanol solution (mass concentration of 2 mg / mL) on the surface of the water film layer, and then post-annealing (temperature of 110 °C, time of 8 min) to prepare a SAM layer;

[0061] (6) Preparing a perovskite layer on the surface of the SAM layer by spin coating;

[0062] (7) preparing an interface passivation layer on the surface of the perovskite layer by spin coating;

[0063] (8) preparing an electron transport layer on the surface of the interface passivation layer by spin coating;

[0064] (9) Preparing a SnO2 layer on the surface of the electron transport layer by ALD;

[0065] (10), preparing an IZO layer on the surface of the SnO2 layer by magnetron sputtering;

[0066] (11) A metal electrode is prepared on the surface of the IZO layer by evaporation to obtain a perovskite crystalline silicon stacked solar cell.

[0067] Example 3

[0068] A perovskite crystalline silicon stacked solar cell, comprising a crystalline silicon bottom cell S1, an ITO tunneling layer S2, and a NiO x Transport layer S3 (x is 2), water film layer S4, SAM layer S5 (Me-4PACz), perovskite layer S6 (Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.73 Br 0.27 )3), interface passivation layer S7 (PI), electron transport layer S8 (PCBM), SnO2 layer S9, IZO layer S10, metal electrode layer S11 (Ag); the preparation method comprises the following steps:

[0069] (1) Obtaining a crystalline silicon bottom cell;

[0070] (2) Preparing an ITO tunneling layer on the surface of the crystalline silicon bottom cell by magnetron sputtering;

[0071] (3) Preparation of NiO on the surface of ITO tunneling layer by magnetron sputtering x Transport layer;

[0072] (4) In NiO x The surface of the transport layer was spin-coated with water (rotation speed of 3000 rpm, time of 30 s) to obtain a water film layer preparatory layer, and the water film layer preparatory layer was sequentially annealed (temperature of 120°C, time of 5 min) and UVO treated (time of 15 min) to obtain a water film layer (thickness of 15 μm);

[0073] (5) spin coating (rotation speed of 3000 rpm, time of 30 s) a Me-4PACz isopropanol solution (mass concentration of 2 mg / mL) on the surface of the water film layer, and then post-annealing (temperature of 110 °C, time of 8 min) to prepare a SAM layer;

[0074] (6) Preparing a perovskite layer on the surface of the SAM layer by spin coating;

[0075] (7) preparing an interface passivation layer on the surface of the perovskite layer by spin coating;

[0076] (8) preparing an electron transport layer on the surface of the interface passivation layer by spin coating;

[0077] (9) Preparing a SnO2 layer on the surface of the electron transport layer by ALD;

[0078] (10), preparing an IZO layer on the surface of the SnO2 layer by magnetron sputtering;

[0079] (11) A metal electrode is prepared on the surface of the IZO layer by evaporation to obtain a perovskite crystalline silicon stacked solar cell.

[0080] Example 4

[0081] A perovskite crystalline silicon stacked solar cell, comprising a crystalline silicon bottom cell S1, an ITO tunneling layer S2, and a NiO x Transport layer S3 (x is 2), water film layer S4, SAM layer S5 (Me-4PACz), perovskite layer S6 (Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.73 Br 0.27 )3), interface passivation layer S7 (PI), electron transport layer S8 (PCBM), SnO2 layer S9, IZO layer S10, metal electrode layer S11 (Ag); the preparation method comprises the following steps:

[0082] (1) Obtaining a crystalline silicon bottom cell;

[0083] (2) Preparing an ITO tunneling layer on the surface of the crystalline silicon bottom cell by magnetron sputtering;

[0084] (3) Preparation of NiO on the surface of ITO tunneling layer by magnetron sputtering x Transport layer;

[0085] (4) In NiO x The surface of the transport layer was spin-coated with water (rotation speed of 2000 rpm, time of 40 s) to obtain a water film layer preparatory layer, and the water film layer preparatory layer was sequentially annealed (temperature of 100°C, time of 10 min) and UVO treated (time of 12 min) to obtain a water film layer (thickness of 20 μm);

[0086] (5) spin coating (rotation speed of 2000 rpm, time of 40 s) a Me-4PACz isopropanol solution (mass concentration of 0.5 mg / mL) on the surface of the water film layer, and then post-annealing (temperature of 110 °C, time of 8 min) to prepare a SAM layer;

[0087] (6) Preparing a perovskite layer on the surface of the SAM layer by spin coating;

[0088] (7) preparing an interface passivation layer on the surface of the perovskite layer by spin coating;

[0089] (8) preparing an electron transport layer on the surface of the interface passivation layer by spin coating;

[0090] (9) Preparing a SnO2 layer on the surface of the electron transport layer by ALD;

[0091] (10), preparing an IZO layer on the surface of the SnO2 layer by magnetron sputtering;

[0092] (11) A metal electrode is prepared on the surface of the IZO layer by evaporation to obtain a perovskite crystalline silicon stacked solar cell.

[0093] Example 5

[0094] A perovskite crystalline silicon stacked solar cell, comprising a crystalline silicon bottom cell S1, an ITO tunneling layer S2, and a NiO x Transport layer S3 (x is 2), water film layer S4, SAM layer S5 (Me-4PACz), perovskite layer S6 (Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.73 Br 0.27 )3), interface passivation layer S7 (PI), electron transport layer S8 (PCBM), SnO2 layer S9, IZO layer S10, metal electrode layer S11 (Ag); the preparation method comprises the following steps:

[0095] (1) Obtaining a crystalline silicon bottom cell;

[0096] (2) Preparing an ITO tunneling layer on the surface of the crystalline silicon bottom cell by magnetron sputtering;

[0097] (3) Preparation of NiO on the surface of ITO tunneling layer by magnetron sputtering x Transport layer;

[0098] (4) In NiO x The surface of the transport layer was spin-coated with water (rotation speed of 4000 rpm, time of 20 s) to obtain a water film layer preparatory layer, and the water film layer preparatory layer was sequentially annealed (temperature of 100°C, time of 10 min) and UVO treated (time of 12 min) to obtain a water film layer (thickness of 10 μm);

[0099] (5) spin coating (rotation speed of 4000 rpm, time of 20 s) a Me-4PACz isopropanol solution (mass concentration of 3 mg / mL) on the surface of the water film layer, and then post-annealing (temperature of 110 °C, time of 8 min) to prepare a SAM layer;

[0100] (6) Preparing a perovskite layer on the surface of the SAM layer by spin coating;

[0101] (7) preparing an interface passivation layer on the surface of the perovskite layer by spin coating;

[0102] (8) preparing an electron transport layer on the surface of the interface passivation layer by spin coating;

[0103] (9) Preparing a SnO2 layer on the surface of the electron transport layer by ALD;

[0104] (10), preparing an IZO layer on the surface of the SnO2 layer by magnetron sputtering;

[0105] (11) A metal electrode is prepared on the surface of the IZO layer by evaporation to obtain a perovskite crystalline silicon stacked solar cell.

[0106] Example 6

[0107] A perovskite crystalline silicon stacked solar cell, comprising a crystalline silicon bottom cell S1, an ITO tunneling layer S2, and a NiO x Transport layer S3 (x is 2), water film layer S4, SAM layer S5 (Me-4PACz), perovskite layer S6 (Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.73 Br 0.27 )3), interface passivation layer S7 (PI), electron transport layer S8 (PCBM), SnO2 layer S9, IZO layer S10, metal electrode layer S11 (Ag); the preparation method comprises the following steps:

[0108] (1) Obtaining a crystalline silicon bottom cell;

[0109] (2) Preparing an ITO tunneling layer on the surface of the crystalline silicon bottom cell by magnetron sputtering;

[0110] (3) Preparation of NiO on the surface of ITO tunneling layer by magnetron sputtering x Transport layer;

[0111] (4) In NiO x The transmission layer surface is sprayed (pressure is 100Kpa, spray speed is 2mm / s, nozzle size is 0.2mm, and NiO x The distance of the transmission layer is 100 μm) water to obtain a water film layer preparation layer, and the water film layer preparation layer is successively annealed (temperature is 100 ° C, time is 10 min) and UVO treated (time is 12 min) to obtain a water film layer (thickness is 15 μm);

[0112] (5) Spraying (pressure of 100 KPa, spraying speed of 2 mm / s) an isopropanol solution of MeO-4PACz (mass concentration of 2 mg / mL) on the surface of the water film layer, and then performing post-annealing (temperature of 100 °C, time of 10 min) to prepare a SAM layer;

[0113] (6) Preparing a perovskite layer on the surface of the SAM layer by spin coating;

[0114] (7) preparing an interface passivation layer on the surface of the perovskite layer by spin coating;

[0115] (8) preparing an electron transport layer on the surface of the interface passivation layer by spin coating;

[0116] (9) Preparing a SnO2 layer on the surface of the electron transport layer by ALD;

[0117] (10), preparing an IZO layer on the surface of the SnO2 layer by magnetron sputtering;

[0118] (11) A metal electrode is prepared on the surface of the IZO layer by evaporation to obtain a perovskite crystalline silicon stacked solar cell.

[0119] Example 7

[0120] A perovskite crystalline silicon stacked solar cell, comprising a crystalline silicon bottom cell S1, an ITO tunneling layer S2, and a NiO x Transport layer S3 (x is 2), water film layer S4, SAM layer S5 (Me-4PACz), perovskite layer S6 (Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.73 Br 0.27 )3), interface passivation layer S7 (PI), electron transport layer S8 (PCBM), SnO2 layer S9, IZO layer S10, metal electrode layer S11 (Ag); the preparation method comprises the following steps:

[0121] (1) Obtaining a crystalline silicon bottom cell;

[0122] (2) Preparing an ITO tunneling layer on the surface of the crystalline silicon bottom cell by magnetron sputtering;

[0123] (3) Preparation of NiO on the surface of ITO tunneling layer by magnetron sputtering x Transport layer;

[0124] (4) In NiO x The transmission layer surface is sprayed (pressure is 200Kpa, spray speed is 10mm / s, nozzle size is 0.5mm, and NiO x The transmission layer is 500 μm) water to obtain a water film layer preparation layer, and the water film layer preparation layer is sequentially annealed (temperature is 100 ° C, time is 10 min) and UVO treated (time is 12 min) to obtain a water film layer (thickness is 15 μm);

[0125] (5) Spraying (pressure of 200 KPa, spraying speed of 10 mm / s) an isopropanol solution of MeO-2PACz (mass concentration of 2 mg / mL) on the surface of the water film layer, and then performing post-annealing (temperature of 120 °C, time of 5 min) to prepare a SAM layer;

[0126] (6) Preparing a perovskite layer on the surface of the SAM layer by spin coating;

[0127] (7) preparing an interface passivation layer on the surface of the perovskite layer by spin coating;

[0128] (8) preparing an electron transport layer on the surface of the interface passivation layer by spin coating;

[0129] (9) Preparing a SnO2 layer on the surface of the electron transport layer by ALD;

[0130] (10), preparing an IZO layer on the surface of the SnO2 layer by magnetron sputtering;

[0131] (11) A metal electrode is prepared on the surface of the IZO layer by evaporation to obtain a perovskite crystalline silicon stacked solar cell.

[0132] Comparative Example 1

[0133] The difference from Example 1 is that no water film layer is prepared.

[0134] Comparative Example 2

[0135] The difference from Example 1 is that in (4), NiO x The surface of the transport layer was spin-coated with water (rotation speed of 3000 rpm, time of 30 s) to obtain a water film layer preparatory layer, and the water film layer preparatory layer was sequentially annealed (temperature of 60° C., time of 3 min) and UVO treated (time of 5 min) to obtain a water film layer.

[0136] Comparative Example 3

[0137] The difference from Example 1 is that in (4), NiO x The surface of the transport layer was spin-coated with water (rotation speed of 3000 rpm, time of 30 s) to obtain a water film layer preparatory layer, and the water film layer preparatory layer was sequentially annealed (temperature of 150° C., time of 20 min) and UVO treated (time of 20 min) to obtain a water film layer.

[0138] Performance Test:

[0139] The spreadability of the perovskite solution coating during the preparation of the perovskite crystalline silicon stacked solar cells of the above-mentioned embodiments and comparative examples was observed and graded, wherein "level one" means that the perovskite solution can be spread evenly, and the area of ​​gaps, holes, and rough surfaces in the film layer accounts for less than 2%; "level two" means that most of the perovskite solution can be spread evenly, and the area of ​​gaps, holes, and rough surfaces in the film layer accounts for 2-5%; "level three" means that the perovskite solution cannot be spread evenly, and the area of ​​gaps, holes, and rough surfaces in the film layer accounts for more than 5%.

[0140] The perovskite crystalline silicon stacked solar cells prepared in the above embodiments and comparative examples were tested for photoelectric conversion efficiency and stability, wherein the photoelectric conversion efficiency was tested by IV test, and the service life was tested by IV test MPPT. The test was continued for 1 hour under a 1Sun light source, and the efficiency retention rate of the photoelectric conversion efficiency after irradiation compared with the photoelectric conversion efficiency before irradiation was calculated (the photoelectric conversion efficiency before irradiation was 100%).

[0141] The test results are shown in Table 1.

[0142] Table 1

[0143] / Spreadability of perovskite solution coating Photoelectric conversion efficiency stability Example 1 Level 1 32.0% 99.2% Example 2 Level 2 31.2% 98.5% Example 3 Level 2 30.0% 97.8% Example 4 Level 2 30.5% 97.6% Example 5 Level 2 28.0% 98.1% Example 6 Level 2 29.4% 97.5% Example 7 Level 2 28.3% 97.7% Comparative Example 1 Level 3 27.1% 82.6% Comparative Example 2 Level 3 26.0% 93.1% Comparative Example 3 Level 3 26.5% 93.8%

[0144] As can be seen from the above, compared with the comparative example, each embodiment of the present invention is x A water film layer is used on the surface, combined with annealing and UVO treatment, to obtain more hydroxyl groups on its surface, more anchored SAM components, modify the SAM components, and finally prepare a uniform perovskite film layer on its surface. By changing the underlying structure of the SAM and then changing the wettability of the SAM, a uniform full coverage of the perovskite film layer on the SAM surface can be achieved, significantly improving the uniformity and stability of the perovskite layer, thereby improving the overall photoelectric conversion efficiency and reliability of the perovskite / crystalline silicon laminated solar cell. The method of the present invention has low cost, simple operation, can be prepared on a large scale, is green and pollution-free, and is suitable for commercial production.

[0145] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the overall effect is better.

[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a perovskite crystalline silicon tandem solar cell, characterized in that: The perovskite crystalline silicon stacked solar cell comprises a crystalline silicon bottom cell, an ITO tunneling layer, a NiO x Transport layer, water film layer, SAM layer, perovskite layer, interface passivation layer, electron transport layer, SnO2 layer, IZO layer, metal electrode layer, x is 1-2; the preparation method comprises the following steps: Step S1, sequentially preparing the ITO tunneling layer, the NiO x Transport layer; Step S2, in the NiO x The surface of the transmission layer is coated with water to obtain a water film layer preparatory layer, and the water film layer preparatory layer is sequentially annealed and UVO treated to obtain the water film layer; Step S3, preparing the SAM layer on the surface of the water film layer; Step S4, preparing the perovskite layer on the surface of the SAM layer; Step S5, preparing the interface passivation layer, the electron transport layer, the SnO2 layer, the IZO layer, and the metal electrode layer in sequence on the surface of the perovskite layer to obtain the perovskite crystalline silicon stacked solar cell.

2. The preparation method according to claim 1, characterized in that: In the step S2, the annealing temperature is 80-120° C. and the time is 5-15 minutes.

3. The preparation method according to claim 1 or 2, characterized in that: In step S2, the UVO treatment time is 10 to 15 minutes.

4. The preparation method according to any one of claims 1 to 3, characterized in that In the step S2, the NiO x The surface of the transmission layer is spin-coated or sprayed with water to obtain the water film layer preparation layer.

5. The preparation method according to claim 4, characterized in that: The spin coating has a rotation speed of 2000-4000 rpm and a time of 20-40 s; and / or The spraying pressure is 100-200 Kpa, the spraying speed is 2-10 mm / s, the nozzle size is 0.2-0.5 mm, and the NiO x The distance of the transmission layer is 100 to 500 μm.

6. The preparation method according to any one of claims 1 to 5, characterized in that In the step S2, the thickness of the water film preparation layer is 10-20 μm.

7. The preparation method according to any one of claims 1 to 6, characterized in that In the step S3, the raw materials of the SAM layer include a main component and a solvent, and the main component includes one or more of Me-4PACz, MeO-4PACz and MeO-2PACz; Preferably, in the raw material of the SAM layer, the mass concentration of the main component is 0.5-3 mg / mL.

8. The preparation method according to claim 7, characterized in that: In the step S3, the raw material of the SAM layer is spin-coated or spray-coated on the surface of the water film layer, and then post-annealing is performed to obtain the SAM layer.

9. The preparation method according to claim 8, characterized in that: The spin coating has a rotation speed of 2000-4000 rpm and a time of 20-40 s; and / or The spraying pressure is 100-200 Kpa, and the spraying speed is 2-10 mm / s; and / or The post-annealing temperature is 100-120° C. and the time is 5-10 minutes.

10. A perovskite crystalline silicon tandem solar cell, characterized in that: The method according to any one of claims 1 to 9 is used to obtain the